Dialogue and doxography in Indian philosophy : points of view in Buddhist, Jaina, and Advaita Vedanta traditions /: points of view in Buddhist, Jaina, and Advaita Vedanta traditions. (2020) - Bouthillette, Karl-Stéphan
No abstract available